Features of Poetic Discourse - Aubakir, S.S.; Bizhkenova, A.Ye. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
This paper provides a description of the comprehension of poetry as discourse, and gives definition to the concept of poetic discourse. Although, discourse especially poetic discourse constantly attracts researcher’s attention, there are still problems that have not been reflected in the scientific works. As it is known, poetic discourse is an important part of communicative practices of modern people; besides it is an integral part of cultural and linguistic reality. Exploring poetic discourse as holistic phenomenon is a great interest both in terms of understanding its own poetic nature and in terms of clarification of the related laws of the existence of communication, language and culture.